A supporting method for living environment measurements with residentsâ participation: development of improvement systems for the living environment by a residentsâ€™ association through preparing the â€œliving environment mapsâ€ part 2 - Miura, M.; Kubota, Tetsu; Inokuma, S.; Nishimura, Y.; Mizuno, A. (2005)
The purpose of this study is to develop improvement systems for the living environment by Residentsâ€™ Associations through preparing the â€œLiving Environment Mapsâ€. As the second stage of this study, this paper examined the supporting methods for living environment measurements with residentsâ€™ participations based on the whole process of the field measurements for noise level and NO2 concentration, which residents actually participated in at the case studies with 3 Residentsâ€™ Associations. Researchersâ€™ supports for explanations and coaches for using noise level meters and capsules for NO2 capture are effective for promoting residentsâ€™ participations to the measurements.